2015
DOI: 10.1007/s10567-015-0193-7
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Mental Health and Well-Being After Parental Intimate Partner Homicide: A Systematic Review

Abstract: When one parent kills the other, children are confronted with multiple losses, involving their attachment figures and their direct living environment. In these complex situations, potentially drastic decisions are made, for example, regarding new living arrangements and contact with the perpetrating parent. We aimed to synthesize the empirical literature on children's mental health and well-being after parental intimate partner homicide. A systematic search identified 17 relevant peer-reviewed articles (13 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 50 publications
0
28
0
2
Order By: Relevance
“…This qualitative interview study was part of a larger project regarding the characteristics, circumstances, and well-being of children who had been bereaved by parental intimate partner homicide in the Netherlands between 1993 and 2012 (Alisic et al, 2017, 2015), approved by the University Medical Center Utrecht Ethics Committee (13/609, 24-12-2013).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This qualitative interview study was part of a larger project regarding the characteristics, circumstances, and well-being of children who had been bereaved by parental intimate partner homicide in the Netherlands between 1993 and 2012 (Alisic et al, 2017, 2015), approved by the University Medical Center Utrecht Ethics Committee (13/609, 24-12-2013).…”
Section: Methodsmentioning
confidence: 99%
“…Three participants met criteria for PTSD at the time of the interview, while 12 reported some PTSD symptoms and eight did not experience PTSD symptoms [measured with the Dutch versions of the Anxiety Disorders Interview Schedule for DSM-IV (Siebelink & Treffers, 2001) or the Structured Clinical Interview for DSM Disorders (Groenestijn, Akkerhuis, Kupka, Schneider, & Nolen, 1999), depending on participants’ age; see Alisic et al, 2015, for details]. One of the children with PTSD also had clinically significant grief symptoms [measured with the Dutch version of the Inventory of Traumatic Grief (Boelen, de Keijser & van den Bout, 2001) and the Inventory of Prolonged Grief for Children and Adolescents (Spuij et al, 2012)].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known about the bereaved children’s circumstances and support needs. A recent systematic review identified only 13 broadly relevant studies worldwide, of which 8 were case studies, and all but two were convenience samples [ 8 ]. Possible reasons for the lack of research and insight include the highly sensitive nature of the topic, repeated changes in children’s living arrangements and contact details after the homicide, dissatisfaction of caregivers with child protection and placement services, and high levels of grief and mental health problems among both children and caregivers, including avoidance of potential reminders.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the activity level determined the speed of information flow within the central nervous system, those disorders affected the efficiency of cognitive and motoric processes. The adolescents exposed to IPV experienced mental health consequences: psychological, social and academic difficulties in accomplishing school assignments 23 .…”
Section: Discussionmentioning
confidence: 99%